2003
DOI: 10.1212/01.wnl.0000068020.85450.8b
|View full text |Cite
|
Sign up to set email alerts
|

N -acetyl-aspartate, total creatine, and myo-inositol in the epileptogenic human hippocampus

Abstract: These data suggest that decreased N-acetyl-aspartate in mesial temporal lobe epilepsy reflects altered mitochondrial metabolism, not merely neuron loss or gliosis. It is hypothesized that the altered N-acetyl-aspartate and creatine metabolism could reflect mitochondrial dysfunction or proliferation of immature glial cells that could contribute to the epileptogenic state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 46 publications
2
57
1
1
Order By: Relevance
“…Absolute quantification of tNAA concentrations revealed, however, that the reduction in the NAA/Cr ratio resulted from decreased tNAA concentrations while Cr concentrations remained unchanged. In addition to clinical in vivo examination, 1 H-MRS has been investigated in vitro (38) and using animal models (39). The study of Petroff et al (38) puts the above results into perspective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Absolute quantification of tNAA concentrations revealed, however, that the reduction in the NAA/Cr ratio resulted from decreased tNAA concentrations while Cr concentrations remained unchanged. In addition to clinical in vivo examination, 1 H-MRS has been investigated in vitro (38) and using animal models (39). The study of Petroff et al (38) puts the above results into perspective.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to clinical in vivo examination, 1 H-MRS has been investigated in vitro (38) and using animal models (39). The study of Petroff et al (38) puts the above results into perspective. In vitro 1 H-MRS of hippocampal specimens at 11.75 T did not reveal a significant association between hippocampal neuron loss and cellular content of NAA, Cr or m-Ins.…”
Section: Discussionmentioning
confidence: 99%
“…42 Thus, astrocytes in the sclerotic hippocampus seem to have a reduced capacity for glutamine synthesis and ammonia detoxification. Indeed, extracellular glutamine levels 43 and cellular glutamine levels 10,44 are reported reduced in the epileptogenic (sclerotic) hippocampus.…”
Section: Astrocytes Specific Enzymesmentioning
confidence: 99%
“…Analysis of the pathology and electrophysiology of 151 hippocampi removed in the Yale surgical series revealed that after surgery, 84% of patients with sclerotic hippocampi had an excellent (Engel class I) outcome. 9 In these sclerotic hippocampi, in addition to a greater than 50% loss of neurons, the glial density is increased by approximately 80% compared to nonsclerotic hippocampi and neurologically normal autopsy controls 10,11 (FIG. 1).…”
Section: Introductionmentioning
confidence: 99%
“…NAA is a metabolite produced within neuronal mitochondria that reflects neuronal density and functional viability. 21,22 Such biochemical-cognitive associations have not been explored in opiateusing populations. This finding and biochemical imaging technique (i.e.…”
Section: Introductionmentioning
confidence: 99%